Boom Sprayer Calibration Tables - Michael J. Mulvaney; Pratap Devkota; Ethan Carter; De Broughton; Mark Mauldin (EDIS)
This 13-page publication is meant to make calibration of boom sprayers easier, and therefore more common, by providing a convenient chart that can be kept in barns, tractor cabs, sprayers, and mix-load facilities for quick reference. Written by Michael J. Mulvaney, Pratap Devkota, Ethan Carter, De Broughton, and Mark Mauldin, and published by the UF/IFAS Agronomy Department, November 2020.